2020
DOI: 10.1002/acr.23998
|View full text |Cite
|
Sign up to set email alerts
|

Large Variability of Frequency and Type of Physical Therapy in Patients in the German Network for Systemic Sclerosis

Abstract: Objective. To determine the type and frequency of physical therapy (PT) prescribed by physicians for patients in the registry of the German Network for Systemic Sclerosis.Methods. The data for 4,252 patients were analyzed using descriptive statistics, chi-square tests, and odds ratios (ORs).Results. Overall, 37.4% of patients (1,590 of 4,252) received PT at the end of a yearly follow-up. The most frequently used type of PT was lymphatic drainage (n = 1,061, 36.8%), followed by exercise therapy (n = 1,047, 36.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
1
6
2
Order By: Relevance
“…Regarding the use of PT, the proportion of 63% over 2 years was somewhat higher than the percentages seen in previous studies, which reported proportions of SSc patients visiting PT during 1 year ranging from 37-58% (6)(7)(8). Firstly, our proportion covered 2 years, whereas for the previous studies (6-8) only 1 year was covered.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Regarding the use of PT, the proportion of 63% over 2 years was somewhat higher than the percentages seen in previous studies, which reported proportions of SSc patients visiting PT during 1 year ranging from 37-58% (6)(7)(8). Firstly, our proportion covered 2 years, whereas for the previous studies (6-8) only 1 year was covered.…”
Section: Discussioncontrasting
confidence: 86%
“…However, improving PT care for SSc patients remains challenging due to a lack of insight into current PT use and a lack of studies on the effectiveness and safety of PT in SSc. The few studies to date that have assessed the frequency of PT use in SSc patients have reported percentages ranging from 37% at the end of a yearly follow-up to between 53% and 58% in the last year (6)(7)(8). Only 1 study evaluated the content of PT as reported by physicians.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the content of physical therapy, our finding that exercise therapy was one of the most frequently used treatment modalities is in line with one German study (8). Our study adds to these results with a more detailed description of the treatment modalities employed.…”
Section: Discussionsupporting
confidence: 85%
“…This is also the case for systemic sclerosis (SSc), a rare, chronic autoimmune disease with multiorgan involvement (5). Physical therapists are among the most frequently visited health professionals in SSc, with the proportion of SSc patients visiting a physical therapist during 1 year ranging between 37% and 58% (6)(7)(8)(9). In the literature, SSc patients have expressed the need for improvement of non-pharmacological care, including physical therapy (10,11).…”
mentioning
confidence: 99%